Other Notable Protein Blotting Methods: A Brief Review - Kurien, Biji T. (Methods Mol Biol, 2015)
Proteins have been transferred from the gel to the membrane by a variety of methods. These include vacuum blotting, centrifuge blotting, electroblotting of proteins to Teflon tape and membranes for N- and C-terminal sequence analysis, multiple tissue blotting, a two step transfer of low and high molecular weight proteins, blotting of Coomassie Brilliant Blue (CBB) stained proteins from polyacrylamide gels to transparencies, acid electroblotting onto activated glass, membrane-array method for the detection of human intestinal bacteria in fecal samples, protein microarray using a new black cellulose nitrate support, electrotransfer using square wave alternating voltage for enhanced protein recovery, polyethylene glycol mediated significant enhancement of the immunoblotting transfer, parallel protein chemical processing before and during western blot and the molecular scanner concept, electronic western blot of matrix-assisted laser desorption/ionization mass spectrometric-identified polypeptides from parallel processed gel-separated proteins, semi-dry electroblotting of peptides and proteins from acid-urea polyacrylamide gels, transfer of silver-stained proteins from polyacrylamide gels to polyvinylidene difluoride (PVDF) membranes and the display of K(+) channel proteins on a solid nitrocellulose support for assaying toxin binding. The quantification of proteins bound to PVDF membranes by elution of CBB, clarification of immunoblots on PVDF for transmission densitometry, gold coating of non-conductive membranes before matrix-assisted laser desorption/ionization tandem mass spectrometric analysis to prevent charging effect for analysis of peptides from PVDF membranes, a simple method for coating native polysaccharides onto nitrocellulose are some of the methods involving either the manipulation of membranes with transferred proteins or just a passive transfer of antigens to membranes. All these methods are briefly reviewed in this chapter.